Tata Laksana Cairan Isotonis pada Pasien Hiponatremia Simptomatik - Luh Putu Dea Sasmita Pralambari; Nyoman Paramita Ayu (PT Dexa Medica, 2025)
A case has been reported of a 66-year-old male patient presenting with decreased level of consciousness, suspected to be suffered from metabolic disorder — hyponatremia. In most cases of symptomatic hyponatremia, administrationof hypertonic fluids is often recommended. However, hypertonic fluid such as 3% NaCl carries a serious risk, the most severe of which is osmotic demyelination syndrome. Therefore, in cases of hypovolemic hyponatremia, some guidelinesrecommend correction with the administration of 0.9% NaCl isotonic saline solution. Precise administration of isotonic saline has been shown to adequately restore the sodium deficit caused by hypovolemia. In this case, following sodiumcorrection, the patient’s level of consciousness improved clinically, and serum sodium increased from 100 mmol/l to 106 mmol/l, and subsequently to 109 mmol/l within 24 hours. This 9 mmol/l increase was within the recommended target of an8–12 mmol/l over 24 hours. Based on these findings, sodium correction using isotonic fluids can be considered as a viable therapeutic option.